The interrelation between cardiometabolic risk biomarkers and clinical features of chronic coronary syndrome in patients with non-alcoholic fatty liver disease - Mykhailovska, N. S.; Stetsiuk, I. O.; Miniailenko, L. E.; Hawker, T. O.; Lisova, O. O.; Grytsay, G. V.; Shershnyova, O. V.; Korylchuk, N. I.; Riabokon, S. S.; Михайловська, Наталія Сергіївна; Стецюк, Ірина Олегівна; Міняйленко, Любов Євгеніївна; et al. (My University, 2022)
that significantly worsens the course of chronic coronary syndrome (CCS). Nowadays it is important to determine the common mechanisms of CCS and NAFLD progression in order to develop a comprehensive and individualized approach to the management of patients with this comorbid pathology. The aim of the study: To study the interrelation between metabolic, pro-inflammatory disorders’ biomarkers and endothelial dysfunction with the clinical features of CCS in patients with NAFLD. Materials and methods: The monocenter double open study in parallel groups’ co-sex. All patients underwent a biochemical study to determine the parameters of carbohydrate, lipid spectrum, functional state of the liver, enzyme-linked immunosorbent assay to determine the content of biomarkers (adiponectin, resistin, insulin, asymmetric dimethylarginine, highly sensitive C-reactive protein), daily Holter ECG monitoring and two-dimensional echocardiography. Results and discussion: In CCS patients with NAFLD a significant decrease in serum adiponectin level was found (by 60% if compared to the selected control group, and by 31.6% if compared to the comparison group; p<0.05) and an increase in resistin level (by 48% if compared to the selected control group, and by 27% if compared to the comparison group; p<0.05). In patients of the main group the ratio of adiponectin/resistin was 4.89 times lower if compared to healthy individuals and 1.48 times lower if compared to CCS patients without liver pathology (p<0.05). There was a significant increase in the HOMA-IR index in CCS patients with NAFLD if compared to both healthy individuals and CCS patients without NAFLD – 5 times and 2.35 times, respectively (p<0.05). Correlation analysis revealed the interrelation between adipocytokine imbalance, endothelial dysfunction markers, systemic inflammation with metabolic disorders, and indicators of liver damage in patients with CCS comorbid with NAFLD. It was found that the level of adiponectin, resistin, ADMA, adiponectin/resistin ratio, HOMA-IR index influences the relative risk of development of atherogenic dyslipidemia, diastolic dysfunction of the LV accompanied by LV hypertrophy, vegetative imbalance, ischemic changes, and thickening of the intima-media complex development. Conclusions: In CCS patients with NAFLD, if compared to patients without NAFLD, a decrease in adiponectin, an increase in resistin, ADMA, HF-CRP, HOMA-IR index is observed. The obtained results of correlation analysis and estimation of relative risk confirm the clinical and pathogenetic role of the identified cluster of metabolic, pro-inflammatory disorders, and endothelial dysfunction in the progression of CCS with concomitant NAFLD.
Keywords: chronic coronary syndrome; non-alcoholic fatty liver disease; biomarkers; interrelation